The handbook of language, gender, and sexuality (Blackwell handbooks in linguistics, 2014)
"Significantly expanded and updated, the second edition of The Handbook of Language, Gender and Sexuality brings together a team of the leading specialists in the field to create a comprehensive overview of key historical themes and issues, along with methodologies and cutting-edge research topics. Examines the dynamic ways that women and men develop and manage gendered identities through their talk, presenting data and case studies from interactions in a range of social contexts and different communities Substantially updated for the second edition, including a new introduction, 24 newly-commissioned chapters, ten updated chapters, and a comprehensive index Includes new chapters on research in non-English speaking countries - from Asia to South America - and cutting-edge topics such as language, gender, and popular culture; language and sexual identities; and language, gender, and socio-phonetics New sections focus on key themes and issues in the field, such as methodological approaches to language and gender, incorporating new chapters on conversation analysis, critical discourse analysis, corpus linguistics, and variation theory Provides unrivalled geographic coverage and an essential resource for a wide range of disciplines, from linguistics, psychology, sociology, and anthropology to communication and gender studies "--